Apolipoprotein A-I deficiency due to a codon 84 nonsense mutation of the apolipoprotein A-I gene. - Matsunaga, T (1991)
The molecular genetic defect of a female patient with apolipoprotein A-I (apoA-I) deficiency and premature atherosclerosis was examined. Her parents were first cousins. Her plasma density fraction from 1.063 to 1.21 g/ml contained no apoA-I on SDS/PAGE and no measurable high density lipoprotein cholesterol. Southern blot hybridization showed no gross abnormality to be present in the patient's apoA-I gene and homozygosity for a haplotype of restriction fragment length polymorphisms in the apoA-I gene region. Sequencing after amplification by PCR revealed a codon 84 nonsense mutation (CAG----TAG, Gln----stop) of exon 4 and a codon 67 missense mutation (GCC----ACC, Ala----Thr) of exon 3 in the patient's apoA-I gene. The data from dot-blot hybridization with allele-specific oligonucleotide probes indicated that she was homozygous for the apoA-I gene with regard to the two mutations. The codon 37 missense mutation was also detected in the apoA-I gene of 6 out of 60 controls, who all had normal levels of apoA-I and high density lipoprotein cholesterol, suggesting that the missense mutation is polymorphic and not associated with apoA-I deficiency. These findings indicate that homozygosity for the apoA-I gene with codon 84 nonsense mutation causes the deficiency of apoA-I and of high density lipoprotein cholesterol in the patient.